A simple jig for the anti-parallel alignment of linacs' lasers. Issue 2 (11th January 2016) - Okkalides, Demetrios
Abstract: Background: Despite crossing at the isocentre, misaligned laser beams may cause significant positioning problems. Purpose: The jig proposed here is to be used in addition to the quality assurance procedures employed with linacs and deals with possible misalignments of transverse lasers. Materials and methods: It is an inverted T construction with a two-sided rectangular, slightly transparent mirror set vertical on a piece of glass serving as its base. The device is carried by a horizontally set spirit-level surface and placed on the couch-top so that the sagittal laser passes through the vertical mirror's plane. Then the therapy couch is translated along the Y direction until a laser beam shines on the corresponding side of the semi-transparent mirror. This spot is marked and is normally the linac's isocentre set through an independent procedure employing a rotating plate. If the laser had been set properly, then its beam should be reflecting back on its source. If not, the alignment can be corrected by rotating and/or translating the laser holder until it does that. At the same time, it should be ensured that the beam does not wander away from the isocentre spot on the mirror. When both are achieved, the beam ends up perpendicular to the linac's axis of rotation, while passing through the isocentre. The procedure can be repeated for the opposite laser. Conclusion: The jig was simple to construct and has been found quite useful in practice. The accuracy of patient positioning will be restricted only by the size of the laser beam's cross-section.